(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1997)
An incomplete skull of Hemisyntrachelus sp. (Cetacea, Delphinidae) is described from the Piacenzian clayey marls of Rio Stramonte (Piacenza, Italy). The new find confirms the abundance of Hemisyntrachelus in the peri-Adriatic area during the Pliocene.